The Influence of Perceived Confirmation and Perceived Usefulness on Continuance Intention to Use Mobile Banking with Satisfaction as a Mediating Variable in Generation Z in Indonesia - Natasya Salsabilla Murti; Dewita Puspawati (Program Pascasarjana STIE Amkop Makassar, 2026)
This research boldly seeks to dissect the impact of perceived confirmation and perceived usefulness on the ongoing intention to utilize mobile banking, with satisfaction acting as a pivotal mediating factor among Generation Z in Indonesia. Employing a quantitative methodology, the study surveyed 150 Generation Z individuals who have engaged with mobile banking services. Data analysis was executed through Structural Equation Modeling—Partial Least Square (SEM-PLS) utilizing SmartPLS 4.0. The findings reveal that perceived confirmation and perceived usefulness significantly influence satisfaction. Moreover, satisfaction profoundly affects the intention to continue using mobile banking. Additionally, satisfaction has proven to be an effective mediator for the effects of perceived confirmation and perceived usefulness on the intention to continue. These results underscore the critical alignment between user expectations and service performance, as well as the perceived advantages for users, in enhancing satisfaction and the longevity of mobile banking usage, especially within Generation Z.